Measuring the Influence of Philosophy on Arab Balaghah: A Critical Study of Amin al-Khuli's Thought - Qudsiyah, Wardah Nailul; Wafi, Hasan Abdul; Syihabuddin, Muhammad; Zenrif, M. Fauzan (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2024)
Abstract: This article aims to explore the relationship between philosophy and balaghah, as well as the mutual influence between the two, focusing on Amin al-Khuli's “Manahij Tajdid Fi al-Nahw Wa al-Balaghah Wa al-Tafsir Wa al-Adab.” The relationship between philosophy and balaghah is a rarely discussed topic, so this article offers a new perspective on the study of Arabic literature and philosophical thought. In this study, the main sources analyzed are al-Khuli's works as well as several relevant articles and books, both those that discuss al-Khuli's thoughts directly and those that highlight the historical development of philosophy and balaghah. The method used is descriptive-analytical, in which the research deeply examines primary and secondary literature related to the topic. The author attempts to identify the elements of philosophy in classical balaghah works, as well as to trace the traces of philosophical thought in the balaghah tradition. The research also examines the important role of the translation of Aristotle's works into Arabic, which enriched the development of both disciplines. The results show that philosophical thought has long been present in the works of balaghah figures. This influence can be seen in written works that combine elements of philosophy and balaghah. Furthermore, the translation of classical Greek philosophical texts by Arab scholars further reinforced the importance of understanding philosophy for balaghah scholars. In conclusion, the relationship between philosophy and balaghah is mutually influential. Abstrak: Penelitian ini bertujuan untuk mengeksplorasi hubungan antara filsafat dan balaghah, serta pengaruh timbal balik antara keduanya, dengan fokus pada karya Amin al-Khuli yang berjudul Manahij Tajdid Fi al-Nahw Wa al-Balaghah Wa al-Tafsir Wa al-Adab. Hubungan antara filsafat dan balaghah merupakan topik yang jarang dibahas, sehingga artikel ini menawarkan perspektif baru dalam kajian sastra Arab dan pemikiran filosofis. Sumber utama yang dianalisis adalah karya-karya al-Khuli serta beberapa artikel dan buku relevan lainnya, baik yang membahas pemikiran al-Khuli secara langsung maupun yang menyoroti perkembangan historis filsafat dan balaghah. Metode yang digunakan adalah deskriptif-analitis dengan menelaah secara mendalam literatur primer dan sekunder yang berkaitan dengan topik. Penulis berupaya mengidentifikasi elemen-elemen filsafat dalam karya-karya balaghah klasik, serta menelusuri jejak pemikiran filosofis dalam tradisi balaghah. Penelitian ini juga mengkaji peran penting penerjemahan karya-karya Aristoteles ke dalam bahasa Arab, yang memperkaya perkembangan kedua disiplin ilmu tersebut. Hasil penelitian menunjukkan bahwa pemikiran filosofis telah lama hadir dalam karya-karya tokoh balaghah. Pengaruh ini dapat dilihat dalam karya-karya tertulis yang menggabungkan elemen-elemen filsafat dan balaghah. Lebih lanjut, penerjemahan teks-teks filosofis Yunani klasik oleh para sarjana Arab semakin memperkuat pentingnya pemahaman filsafat bagi para ahli balaghah. Kesimpulannya, hubungan antara filsafat dan balaghah saling mempengaruhi satu sama lain.